FAKTOR FAKTOR YANG MEMPENGARUHI KEPUTUSAN BERKUNJUNG PADA WATERPARK TOP 100 BATU AJI - Yogitanto, Yogitanto; Simanjuntak, Jontro (SCIENTIA JOURNAL, 2021)
a tourist spot that has a lot of appeal for tourists deciding to visit must have a large recreation area or playground so that tourists can spend their time on vacation or recreation with friends or family. This type of research is quantitative by using a causal relationship to determine how the effect of promotion, facilities and service quality on the decision to visit the Waterpark Top 100 Batu Aji. The population in this study were Waterpark visitors in the March 2020 period totaling 5,388 visitors, with a sample size of 373. The sampling technique used nonprobability sampling method with accidental sampling technique. Data collection using a questionnaire and Google form with a Likert measurement scale. The data were analyzed using IMB SPSS 21. The results showed that there was an effect of promotion on the decision to visit with a value of t (7,121)> t table (1.9719), there was an effect of facilities on the decision to visit with a value of t count (5.989)> t. Table (1.9719), there is an effect of service quality on the decision to visit with the value of t count (6.753)> t table (1.9719), and there is an effect of promotion, tariff and service quality on the decision to visit with the value of F count (187.519)> F table (2.64).